Pengaruh Pola Makanan Gorengan dan Makanan Panggang terhadap Tingkat Insidensi Kanker di Kalangan Usia Remaja dan Dewasa Muda - Juanta, Palma; Anggellino, Jasen (IAI Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of fried and grilled food consumption patterns on the incidence of cancer among adolescents and young adults. Data were collected from 100 respondents using a structured questionnaire and purposive sampling method. Logistic regression analysis was employed to identify the relationship between unhealthy eating habits, such as consuming fried and grilled foods, and the potential risk of cancer incidence. The findings reveal that the consumption patterns of fried and grilled foods significantly contribute to the increased risk of cancer, with frequent use of reused cooking oil and grilled food consumption emerging as dominant factors. These results align with the Theory of Biological Balance, which posits that biological imbalance caused by the intake of harmful substances, such as acrylamide and PAHs, can elevate the risk of carcinogenesis. This study highlights the urgent need for nutritional education and the promotion of healthy eating habits to reduce exposure to carcinogenic substances, particularly among adolescents and young adults, to prevent future cancer cases.